2018
DOI: 10.1155/2018/1630751
|View full text |Cite
|
Sign up to set email alerts
|

Lycium europaeum Extract: A New Potential Antioxidant Source against Cisplatin‐Induced Liver and Kidney Injuries in Mice

Abstract: This study was designed to assess the protective effects of Lycium europaeum methanol extract (LEM) on liver and kidney injuries induced by cisplatin. The phytochemical composition, the antioxidant activity, and hepatorenal injury biomarkers were investigated. Results revealed that LEM exhibited a significant antioxidant activity in vitro on DPPH radical and H2O2 scavenging assays. In the animal studies, treatment with LEM significantly reduced the effects of cisplatin intoxication on serum liver biomarkers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…The results of the present study is in agreement with the findings of Yadappa et al (2017) and Rjeibi et al (2018), who reported that, crude extract and partially purified protein fractions intoxication results in deleterious disorganization and necrosis of hepatic cells and the diagnosed impact is in general established on the type of toxins, purification as well as dose level. Here, the hepatic histopathological impact was diagnosed in all the studied toxins and with extra powerful impact after intoxication with protein fraction of 1kDa (Fig.…”
Section: O N L I N E C O P ÿsupporting
confidence: 93%
“…The results of the present study is in agreement with the findings of Yadappa et al (2017) and Rjeibi et al (2018), who reported that, crude extract and partially purified protein fractions intoxication results in deleterious disorganization and necrosis of hepatic cells and the diagnosed impact is in general established on the type of toxins, purification as well as dose level. Here, the hepatic histopathological impact was diagnosed in all the studied toxins and with extra powerful impact after intoxication with protein fraction of 1kDa (Fig.…”
Section: O N L I N E C O P ÿsupporting
confidence: 93%
“…Moreover, lentinan also inhibits the proliferation of HeLa and A549 cells [117]. In addition, Ganoderma lucidum polysaccharides and Lycium barbarum polysaccharides can increase the activities of antioxidant enzymes and reduce the levels of oxidative stress and lipid peroxidation, thereby protecting against cisplatin-induced nephrotoxicity [118]. Lycium europaeum Linn is a well-known medicinal plant and is a source of polysaccharides with antioxidant activities in vivo and in vitro [119].…”
Section: Polysaccharidesmentioning
confidence: 99%
“…Catalase, an enzyme with potent antioxidant properties, is mainly located in peroxisomes [33]. Previous studies reported the suppressive effect of cisplatin on catalase activity in mice kidney [34,35]. In addition, Sirt1 overexpression prevented oxidative stress-induced tubular cell apoptosis by increasing catalase level [36].…”
Section: Discussionmentioning
confidence: 99%